2017
DOI: 10.1080/01902148.2017.1386735
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent effects of tadalafil and roflumilast on ovalbumin-induced airway hyperresponsiveness in guinea pigs

Abstract: The selective PDE4 and PDE5 inhibitors alleviated allergic airway inflammation, with more significant effects at the higher doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Roflumilast protected against CSE-induced cell death in Beas-2B cells, suggesting that roflumilast might do well in COPD treatment (Kyung et al, 2018 ). In vivo efficacies of roflumilast in airway inflammatory models suggested that roflumilast displayed bronchodilatory activity in spasmogen-challenged rats and guinea pigs and exhibited dose-dependent efficacy in airway hyperresponsiveness associated with eosinophilic inflammation evoked by ovalbumin (OVA) (Urbanova et al, 2017 ). Izikki et al found that roflumilast could also inhibit hypoxia- and monocrotaline-induced severe pulmonary vascular remodeling and hypertension in rats (Izikki et al, 2009 ).…”
Section: Approved Pde4 Inhibitors For the Treatment Of Inflammatory Dmentioning
confidence: 99%
“…Roflumilast protected against CSE-induced cell death in Beas-2B cells, suggesting that roflumilast might do well in COPD treatment (Kyung et al, 2018 ). In vivo efficacies of roflumilast in airway inflammatory models suggested that roflumilast displayed bronchodilatory activity in spasmogen-challenged rats and guinea pigs and exhibited dose-dependent efficacy in airway hyperresponsiveness associated with eosinophilic inflammation evoked by ovalbumin (OVA) (Urbanova et al, 2017 ). Izikki et al found that roflumilast could also inhibit hypoxia- and monocrotaline-induced severe pulmonary vascular remodeling and hypertension in rats (Izikki et al, 2009 ).…”
Section: Approved Pde4 Inhibitors For the Treatment Of Inflammatory Dmentioning
confidence: 99%
“…The remaining four sensitized groups were treated with theophylline at the doses of 5, 10, or 20 mg/kg, given intraperitoneally for one day (single dose) or for seven days (seven doses) from the 15 th day of sensitization. Detailed information about sensitization procedure can be found in our previous publication (29). Samples of blood were taken to the K 2 EDTA tubes immediately after sacrificing the animals.…”
Section: Application Of the Methodsmentioning
confidence: 99%
“…34 The significant suppression of both in vivo and in vitro contractile responses to the cumulative doses of acetylcholine and histamine in ovalbumin-sensitized animals was associated with decreased numbers of circulating leukocytes and eosinophils and concentrations of interleukin (IL)-4, IL-5 and TNF-α in the lung homogenate. 35 However, Banner and Page failed to show any significant effects of acute or chronic administration of PDE5 inhibitor in ovalbumininduced eosinophil infiltration in guinea pigs. 36 PDE7 is present in the soluble fraction of T cells, both CD4 + and CD8 + , and controls intracellular levels of cAMP.…”
Section: Dovepressmentioning
confidence: 97%